Answer:
B. 3x^2 - 2x - 1.
Step-by-step explanation:
(f + g)x = f(x) + g(x)
= -4x + 3 + 3x^2 + 2x - 4
Adding like terms we get the answer:
= 3x^2 - 2x - 1.
i cant understand the question
Sorry pls explain
Answer:
<em>See the Venn diagram attached</em>
<u>Numbers given:</u>
- <em>Total</em>: 100
- Either a cat of a fish: 70
- Cat: 46
- Cat and fish: 16
<u>Neither a cat or a fish:</u> 100 - 70 = 30
<u>Fish:</u> 70 - (46 + 16) = 70 - 62 = 8
<u>Required probabilities are:</u>
- a) P(neither) = 30/100 = 0.3
- b) P(f) = (16 + 8)/100 = 0.24
- c) P(f not c) = 8/100 = 0.08
I've attached the graphs to this answer. I hope they help.